The Effect of Adding Ecoenzyme to Corn-Based Trichoderma asperellum Formula on the Biomass of Rice Sprouts - Sagurung, Mariance Dartiani; Anhar, Azwir (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Improving rice productivity is a key priority to meet the increasing national food demand. This study aims to examine the effect of ecoenzyme addition to a Trichoderma asperellum-based corn medium on the biomass of rice seedlings of the Bujang Marantau variety. The research was conducted using a Completely Randomized Design (CRD) with five ecoenzyme concentration treatments (0%, 20%, 40%, 60%, and 80%) and five replications. Parameters observed were fresh weight and dry weight of seedlings after 14 days of treatment. Data were analyzed using ANOVA at a 5% significance level and followed by Duncan’s New Multiple Range Test (DNMRT). The results showed that ecoenzyme application did not significantly affect the fresh or dry weight of the rice seedlings. The highest fresh weight was found at 20% concentration, while the highest dry weight was at 80%. It is concluded that ecoenzyme has not demonstrated effectiveness in enhancing seedling biomass during the early growth stage, possibly because seedlings still rely on internal food reserves. The findings suggest that ecoenzyme may be more suitable for improving soil quality rather than directly stimulating early plant growth. Further research is recommended to optimize dosage, application methods, and appropriate growth stages for maximum benefit.